The contingent effect of state participation on the dissolution of international joint ventures: A resource dependence approach - Mohr, Alexander; Wang, Chengang; Fastoso, Fernando (Journal of International Business Studies, 2016)
We adopt a resource dependence approach to explain the effect of state participation on the dissolution of international joint ventures (IJVs). While resource dependence theory (RDT) has been used to explain the formation of IJVs, we propose an extension of the theory to explain their dissolution. We do so by highlighting the match between foreign firms’ resource needs (resource hierarchy) and the resource provision roles of state-controlled vs private local partners (resource profiles). We further argue that the effect of state participation on the dissolution of IJVs is moderated by foreign firms’ host country experience and IJV age. We test our hypotheses by using data on 623 IJVs in China. Our results show that state participation reduces the risk of IJV dissolution and that the strength of this effect differs depending on the type of state-controlled actor that is involved in an IJV. We also find that host country experience and IJV age moderate the effect of state participation on IJV dissolution. These findings enhance our understanding of IJV dissolution and contribute to the development of RDT.